O ensino de probabilidade no contexto da BNCC e à luz dos princípios da teoria da aprendizagem significativa crítica - Vieira, Luis Duarte (2020)
This text refers to a master's dissertation, constituting by an investigative study in the professional master's course in Science and Mathematics Teaching of the Graduate Program in Science and Mathematics Teaching (PPGECM), from the University of Passo Fundo (UPF). The problem that generated the present study considers our country, new educational context , marked by BNCC and the orientation that all education process must be organized to develop skills. This scenario requires criticism from teachers, and, more than ever, the need to guarantee learning processes, considered and defined is an imperative. Such a necessity, has been sought the theoretical contribution in the Theory of Critical Meaningful Learning (TASC), by Marco Antônio Moreira, in order to answer the following question: “What are the potentialities of a didactic sequence, structured from the Theory of Critical Meaningful Learning? , in a BNCC context, in the view of mathematics teachers? ”. To answer this question, an educational product have been built, a didactic sequence to address the basic concepts of probability, for the sixth year of Elementary School. The proposal developed in the light of the principles of TASC, assumed as a powerful methodological way to generate related and critical learning, and is found in eleven meetings. This proposal, due to the COVID-19 pandemic, was presented to mathematics teachers through an online course, carrying out a qualitative research and selected as an action research, with the aim of analyzing, from the perspective of teachers of mathematics, a didactic sequence, based on the principles of Critical Meaningful Learning Theory (TASC), of concepts of probability for the sixth year of Elementary Education in the context of BNCC implementation. To this end, the data obtained through a questionnaire and structured specifications analyzed in four categories of analysis: methodology, applicability, learning processes and various considerations about the educational product. The results obtained indicate that the product has a use, is applicable to elementary school students, is related to the principles of TASC and can generate relevant and critical learning. Finally, it should be noted that this dissertation is accompanied by the educational product developed, acess